Enhancing Repurchase Intention at Warung Kopi Tepi Sungai Depok: The Role of Customer Experience - Simanihuruk, Maidar; Kusumawardhani, Yuviani; Audilla, Lovita Susan (E-Journal of Tourism; Volume 9 Number 1 (March 2022)DO - 10.24922/eot.v9i1.82285, 2022)
The most important stage in winning customers' hearts is through experience, building a customer experience is an essential part of any marketing strategy. The higher the impact on customer pleasure and the willingness to return and acquire the products sold, the better the customer experience. Warung Kopi Tepi Sungai Depok has various advantages despite its less-than-ideal location. It provides guests with comfort and a peaceful rural setting. The purpose of this research is to see how customer experience affects repurchase intent at Warung Kopi Tepi Sungai Depok. Quantitative methods were employed in the research to gather more comprehensive, valid, reliable, and objective data. A total of 101 customers who visited the café were included in the sample. Both factor and regression analysis was employed in the data analysis. Customer experience had a substantial impact on repurchase intention (t = 8.356 > t table with a significance of 0.000 (? < 0.05). With its interior design and unique style, the customer experience at Warung Kopi Tepi Sungai Depok has a dominant influence on influencing repurchase intention, and consumers are interested in returning to this place. The author makes a suggestion, advising that more attention be paid to and development of the website be done in order to establish direct contacts with clients. This cafe has to improve its services, offer new menu items, and keep its facilities clean. Then Warung Kopi Tepi Sungai Depok will be the top option of the customers. Keywords: Repurchase Intention, Customer Experience, Revisit Intention